Modified-release drug delivery technology. - Rathbone, Michael J., 1957- (Drugs and the pharmaceutical sciences, 2013)
This two volume Second Edition describes the anatomical, physiological, pharmaceutical, and technological aspects of delivery routes, found in areas like:Oral Ocular Dermal and transdermal VaginalColonic Oral mucosal Nasal PulmonaryProviding insight and critical assessment of the many available and emerging modified release drug delivery systems for their current and future value, topics include:Intellectual property rights and regulatory issues and challengesosmotic systems and Qtrol. Qdis. Matrix Systemsthiolated polymers for CR, Oradur. IDD technology, and chronotherapy technologyOral-lynTM.